Risk of cancer associated with residential exposure to asbestos insulation: a whole-population cohort study. (November 2017) - Korda, Rosemary J; Clements, Mark S; Armstrong, Bruce K; Law, Hsei Di; Guiver, Tenniel; Anderson, Philip R; Trevenar, Susan M; Kirk, Martyn D
Summary: Background: The health risks associated with living in houses insulated with asbestos are unknown. Loose-fill asbestos was used to insulate some houses in the Australian Capital Territory (ACT). We compared the incidence of mesothelioma and other cancers in residents of the ACT who did and did not live in these houses. Methods: Our cohort study included all ACT residents identified using Medicare enrolment data. These data were linked to addresses of affected residential properties in the ACT to ascertain exposure. We followed up residents by linking data to the Australian Cancer Database and National Death Index. Outcomes were diagnosis of mesothelioma and selected other cancers. Effects were estimated for males and females separately using standardised incidence ratios (SIRs), adjusting for age and calendar time of diagnosis. Findings: Between Nov 1, 1983, and Dec 31, 2013, 1 035 578 ACT residents were identified from the Medicare database. Of these, 17 248 (2%) had lived in an affected property, including seven (2%) of 285 people diagnosed with mesothelioma. The adjusted incidence of mesothelioma in males who had lived at an affected property was 2·5 times that of unexposed males (SIR 2·54, 95% CI 1·02–5·24). No mesotheliomas were reported among females who had lived at an affected property. Among individuals who had lived at an affected property, there was an elevated incidence of colorectal cancer in women (SIR 1·73, 95% CI 1·29–2·26) and prostate cancer in men (1·29, 1·07–1·54); colorectal cancer was increased, although not significantly, in males (SIR 1·32, 95% CI 0·99–1·72), with no significant increase in the other cancers studied. Interpretation: Residential asbestos insulation is likely to be unsafe. Our findings have important health, social, financial, and legal implications for governments and communities in which asbestos has been used to insulate houses. Funding: ACT Government.